Metachronous multiple primary malignancies: a case report of colon and thyroid cancer - Bojorquez, Kimberly O.; Camacho, Leonel; González, Mariana; Medina, Luis F.; Geraldo, Laura M.; Chávez, Jesús A.; Vidaurri, Karla P.; García, Roberto; Bojórquez, Dylan A.; Macedo, Ricardo; Garibay, Leobardo D. (International Journal of Research in Medical Sciences, 2024)
Cancer remains a challenging disease for our profession despite the medical and technological advances achieved in recent years. This challenge increases when we encounter multiple primary tumors that significantly modify the prognosis of our patients.